2013
DOI: 10.1152/ajpregu.00387.2012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal restructuring of the ground squirrel gut microbiota over the annual hibernation cycle

Abstract: Many hibernating mammals suspend food intake during winter, relying solely on stored lipids to fuel metabolism. Winter fasting in these species eliminates a major source of degradable substrates to support growth of gut microbes, which may affect microbial community structure and host-microbial interactions. We explored the effect of the annual hibernation cycle on gut microbiotas using deep sequencing of 16S rRNA genes from ground squirrel cecal contents. Squirrel microbiotas were dominated by members of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
204
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(218 citation statements)
references
References 66 publications
13
204
1
Order By: Relevance
“…The positive correlation between the butyrate concentration and Firmicutes relative abundance is not surprising, given that taxa within the Firmicutes are the primary butyrate producers in the gut (45). A similar correlation was found previously for active and hibernating thirteen-lined ground squirrels (10). Firmicutes relative abundance is correlated with diet-induced obesity in mice (20,24,25); however, no correlations between body condition and butyrate concentration or Firmicutes relative abundance were detected in this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The positive correlation between the butyrate concentration and Firmicutes relative abundance is not surprising, given that taxa within the Firmicutes are the primary butyrate producers in the gut (45). A similar correlation was found previously for active and hibernating thirteen-lined ground squirrels (10). Firmicutes relative abundance is correlated with diet-induced obesity in mice (20,24,25); however, no correlations between body condition and butyrate concentration or Firmicutes relative abundance were detected in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have investigated the gut microbiota of hibernators (7)(8)(9), and even fewer have done so using modern techniques (i.e., 454 pyrosequencing) (10,11). Hibernation alters microbial diversity, dominant taxa, and metabolic production in thirteenlined ground squirrels (Ictidomys tridecemlineatus) (10) and arctic ground squirrels (11) compared to summer squirrels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extended periods of host fasting likely select for microbes that are able to degrade and subsist on host-derived substrates such as mucins and other glycoproteins (2)(3)(4). Indeed, several studies have revealed a profound effect of fasting on the gut microbiota.…”
mentioning
confidence: 99%
“…However, the Syrian hamster is a facultative hibernator that exhibits relatively short torpor bouts (3 to 4 days) and eats during IBAs, both of which may diminish effects of hibernation on the gut microbiota. Carey et al (4) were the first to survey the gut microbiota of an obligate seasonal hibernator, the thirteen-lined ground squirrel (TLS; Ictidomys tridecemlineatus), using next-generation DNA sequencing techniques. Their results clearly indicate significant seasonal changes in gut microbial diversity and composition.…”
mentioning
confidence: 99%